Ventilation Structure Improvement of Induction Motor Using Multiphysics Simulations - Yujiao Zhang; Xiongfeng Huang; Tao Huang; Jiangjun Ruan; Xiaowen Wu (Institute of Advanced Engineering and Science, 2012)
Temperature rise analysis has significant impact in the design of air-cooled asynchronous induction motor. However, the affection cannot be accurately evaluated by using traditional empirical curves method due to the complexity of the inductor architecture. Considering Joule’s losses in stator windings and the induced eddy current in squirrel cages, and heat dissipation by air convection and solid conduction, in this paper a 3-D coupled-field finite-element method (FEM) is investigated to demonstrate the temperature distribution. The Joule’s losses calculated by 3-D eddy- current field analysis are used as the input for the thermal field analysis, which is deeply dependent on accurate air fluid field analysis. A novel multi-component fluid model is employed to deal with the influence of rotor rotation upon the air convection. The simulation results show the fatal influence of the ventilation structure and the effectiveness of the proposed cooling improvement way. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.605